Use of information support for marketing in tourist enterprises - L. V. Tranchenko; N. V. Tereshchuk; R. I. Lopatiuk; O. M. Tranchenko (Kazimierz Wielki University, 2021)
Every year Ukraine integrates more and more into the world economic economy. Tourist services are one of the most important socio-economic sectors of the world economy. However, Ukraine, having a variety of tourism resources, has little experience in this area. For these reasons, the relevance of the article on the promotion of tourist services is determined. The article investigates the means of promoting tourist services, determining the theoretical and methodological principles of building an effective process of marketing communications at the enterprises of the tourist sphere. It is proved that in order to achieve the effect of synergy, the main principle when deciding on the use of several means of communication is the choice of one means as the main and several - auxiliary. The main thing is to be able to independently and effectively influence consumers. Auxiliary - should fill possible gaps in the reach of the target audience, supporting the main means of communication.